Analisis Return Reksa Dana Syariah Berdasarkan Domestic Macroeconomics dan Foreign Macroeconomics - Dwi Putri Restuti; Bayu Tri Cahya (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2023)
The investment trend of Islamic mutual funds is very interesting in the era of globalization. Sharia mutual funds are the right investment solution because their operations are free from elements of maysir, gharar and usury. In addition, ease of access and reach is also influenced by the application of technology. Investors simply monitor the development of investment instruments using mobile phones. Based on this phenomenon, it is necessary to analyze the various factors that influence the development of Islamic mutual funds so that investors can obtain maximum returns. These influential factors can be domestic macroeconomic factors (inflation, exchange rates and the BI Rate) and foreign (Dow Jones Islamic Market Index). Therefore, this study aims to determine the effect of inflation, exchange rates, the BI Rate and the Dow Jones Islamic Market Index on the return of Islamic mutual funds. A quantitative approach was adopted in the research along with the sample selection using the Purposive Sampling method. So that the population is all Islamic mutual funds registered with the Financial Services Authority with a sample of 17 Islamic mutual funds. Based on multiple linear regression analysis, the results show that: 1) inflation has a partially significant effect on the return of Islamic mutual funds, 2) the exchange rate has no significant effect partially on the return of sharia mutual funds, 3) the BI Rate has no significant effect partially on the return of sharia mutual funds, and 4) the Dow Jones Islamic Market Index has a partially significant effect on the return of Islamic mutual funds. The use of foreign stock indexes (Dow Jones Islamic Market Index) is a novelty in this study.